Strategi Pengembangan Pariwisata Di Kabupaten Pasaman Menggunakan Model Manajemen Perubahan Lewin’s Change - Syafran, Syafran; Eliza, Meria; Harissman, Harissman (Institut Seni Indonesia Padangpanjang, 2024)
Pasaman regency is one of 19 regencies in west Sumatera province. Based on the data that released by centre of statistic institution of west Sumatera, Pasaman regency stated as the second lowest of human development indeks (IPM). One of the three criterias of IPM indeks is economic and welfare of the society. One of the ways in growing the economic and welfare of the society in this regency is developing its tourism. Pasaman regency has a big potential to develop its tourism. It has a beautiful nature, waterfalls, geopark, sport tourism, culture, cullinery etc. unfortunately, all of its potentials has not impacted to the welfare of the society in this regency. Based on this situation it needs to do the organizational development by implementing the change management that proposed by kurt lewin in managing the tourism. This research used qualitative descriptive method where in collecting data used library research, studying the datas that published and also interviewing the related persons. the result of the research shown that the tourism of Pasaman regency should develop by 8 steps of change theory. They are; establish a sense of urgency, form a coalition, create new vision, communicate the vision, empower others by removing barriers, create and reward short-term